Socio-Labor Competence Related with the Formative and Labor Level of the Vocational Education Students from Ceuta - Sánchez-Bolívar , L.; Escalante-González , S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
One of the main aspects, during the student training process and its insertion in the labor market, is its level of social development. Through this study, with a descriptive, exploratory and cross-sectional design; the self-perceived socio-labor skills by the professional training students of a Ceuta institute are analyzed. The sample consisted of 100 individuals (86 women and 14 men). The instrument used was the Test of sociopersonal factors for the labor insertion of the young people of Martínez-Rodríguez & Carmona (2010). Regarding the level of studies, students who come from higher cycles of vocational training have a higher level of socio-labor skills than students who access other degrees. Regarding the work situation of students, students who work have higher levels of socio-labor skills than unemployed students.